Transformasi digital melalui implementasi shopee dan sistem pencatatan pesanan untuk meningkatkan efisiensi UMKM Toko Plastikku - Niken Sekarningtyas; Rahandika Ivan Adyaksana; Vidya Vitta Adhivinna (Department of Accounting Universitas PGRI Yogyakarta, 2026)
This activity is motivated by the low level of digital technology utilization in marketing and order recording systems among Micro, Small, and Medium Enterprises (MSMEs), particularly at Toko Plastikku MSME. The purpose of this study is to analyze how the implementation of digital marketing through e-commerce platforms and an Excel-based order recording system can assist MSME actors in improving business efficiency and effectiveness. The method used is an assistance approach carried out through several stages, namely observation, problem identification, solution planning, Shopee account creation and management, and implementation of an order recording system. The results show that after the assistance process, MSME actors are able to utilize the Shopee platform to expand market reach and increase sales potential. In addition, the implementation of an Excel-based recording system helps manage order data more systematically, accurately, and efficiently. However, challenges remain in terms of time management and adaptation to digital technology, which require continuous assistance. Therefore, this activity contributes to improving operational efficiency and enhancing MSME competitiveness in the digital era.